The Influence of Emotional Intelligence on Learning Motivation for Students at Buddhist College - Wistina Seneru; Sidartha Adi Gautama; Widiyanto Widiyanto; Ayu Andriyaningsih; Ine Yudhawati (Syntax Corporation, 2023)
The research aims to investigate the influence of emotional intelligence on students' learning motivation. Conducted at Jinarakkhita Buddhist College among second-semester students, this study seeks to establish the significant relationship between emotional intelligence and the level of learning motivation. Utilizing a quantitative approach, the study involves data collection from second-semester students at Jinarakkhita Buddhist College using a research instrument that has undergone validity and reliability testing. Statistical analysis is performed to test hypotheses and assess the association between emotional intelligence and learning motivation. The findings of this research will contribute to a deeper comprehension of the significance of emotional intelligence in shaping students' learning motivation. The implications of this study can provide valuable information for educational institutions to enhance the development of students' emotional intelligence and learning motivation.